Complete nucleotide sequence and genome organization of red clover associated virus 1 (RCaV1), a putative member of the genus Waikavirus (family Secoviridae, order Picornavirales) - Koloniuk, Igor; Fránová, Jana (Archives of virology, 2018)
Using high-throughput sequencing, a novel waikavirus was identified in a mixed virus infection of red clover (Trifolium pratense L.). Its complete genomic sequence was determined and characterized. The virus, tentatively named red clover associated virus 1 (RCaV1), is phylogenetically related to members of the genus Waikavirus (family Secoviridae, order Picornavirales).
Keywords: satelitní viry; Sequence Analysis, DNA; Waikavirus; genom virový; Phylogeny; otevřené čtecí rámce; Base Sequence; nemoci rostlin; Genome, Viral; Molecular Sequence Data; molekulární sekvence - údaje; sekvenční analýza DNA; Trifolium; Open Reading Frames; fylogeneze; Satellite Viruses; Plant Diseases; sekvence nukleotidů